Elementary school teachers’ exposure to mobbing - Serkan Akgün; Yeliz Temli-Durmuş (Elementary Education Online, 2023)
Frequency of exposure to mobbing among elementary school teachers working in central Uşak was investigated in the study. In total 347 elementary school teachers who are working in centre of Uşak voluntarily participated in the study. As data collection tool “Mobbing Scale” second version developed by Demirci (2014) was administered. Nonparametric Test was carried out to analyse non-parametric data set. Mann Whitney U-test and Kruskal Wallis H-test were used in the study. Marital Status and Mobbing Level did not show statistically significant relationship. The factor named as Quality of Life and Professional Status and gender show statistically significant relationship; male elementary school teachers face to mobbing more frequently than female classroom teachers. As for teaching experiences, 6-10 years experienced elementary school teachers’ exposure to mobbing frequency higher than 16-20 years, 21-25 years, 26-30 years, and 31-35 years experienced teachers. Elementary school teachers with 26-30 years teaching experiences have lower mobbing frequency than other groups.